Exhumation history of the Hengchun Ridge and its implications for Taiwan orogenic processes - Tan, Pingchuan; Ding, Weiwei; Li, Jiabiao (Frontiers in Earth Science, 2022)
The orogenic evolution of Taiwan is thought to have occurred with a steady and southward propagating trend since the Late Miocene. Recent studies suggest a two-stage collision for the Taiwan orogen and that the collision occurred simultaneously along the entirety of the island of Taiwan. To test this hypothesis, we evaluated 270 bathymetry profiles normal to the trench to constrain variations in the width, length, and crest of the Taiwan accretionary prism from the northern Central Ridge to the southern Hengchun Ridge. South of Taiwan Island, a gradual increase in the width and elevation of the accretionary prism of the Hengchun Ridge is noted. Assuming that the uplift of Hengchun Ridge is dominated by the accretion of hyperstretched continental crust (HSCC), we estimated the uplift rate of the ridge (ca. 0.3 km/Ma) based on a linear regression between the HSCC and the observed depth of the prism crest. Using this uplift rate, we forward modeled the prism crest depth variations from 19.7°N to 23.5°N, and compared these values to observations. The model gives a good match to observations of the Hengchun Ridge, but significantly deeper depths to the north of Hengchun Peninsula. This suggests that the Taiwan orogeny had two stages: the first stage was dominated by structurally underplated HSCC, and the second is a combination of the arrival of the continental shelf and arc–continent collision. In addition to the widely accepted arc–continent collision, our study suggests that both the location and orientation of the continent–ocean boundary play important roles in orogeny.